Trends in traditional and complementary medicine practices in Turkey: Results of two consecutive surveys 2012-2018 - Okka, Berrin; Durduran, Yasemin; Duman, Ipek; Ery?lmaz, Aysenur (Journal of the Pakistan Medical Association, 2022)
Objective: To determine the knowledge, opinions, experiences and trends regarding herbal treatment, traditional medicine and other complementary and alternative medicine. Methods: Two cross-sectional studies were conducted at Meram Faculty of Medicine Hospital, Konya, Turkey, in 2012 and 2018, comprising subjects of either gender aged >18 years. Data was collected using a survey form prepared in the light of relevant literature. Data was summarised and compared between the two studies. Results: Of the 810 subjects in the two studies, there were 405(50%) in 2012 with a mean age of 32.5±14.0 years, while the remaining 405(50%) were part of the 2018 study with a mean age of 34.4±13.8. There were significant differences between the two group of subjects about the use and indications of traditional and complementary medicine as those who believed traditional and complementary medicine was proper to use increased and those who believed it should not be used decreased significantly (p<0.001). There was a twofold increase in the use of social media as the source of relevant information (p<0.001). Conclusion: Significant changes in trends related to the use of traditional and complementary medicine between 2012 and 2018 were observed. Key Words: Complementary medicine, Traditional medicine, Herbal therapy. Continue...